The story of the green PM - Deabil, Eman (2024)
The book review introduces the concept of the Green PMO (Project Management Office), an initiative led by Eman Deabil to integrate sustainability into project management practices. It explores how the Green PMO was conceived, driven by global challenges like climate change and social inequalities, and developed into a collaborative book involving professionals from over 20 countries. The Green PMO provides practical frameworks, strategies, and case studies to help PMOs embed sustainability in their operations. By uniting project managers globally, it aims to drive meaningful, lasting change while fostering thought leadership and networking opportunities in sustainable project management.